2021
DOI: 10.1097/hjh.0000000000002621
|View full text |Cite
|
Sign up to set email alerts
|

Routine assessment of cognitive function in older patients with hypertension seen by primary care physicians: why and how—a decision-making support from the working group on ‘hypertension and the brain’ of the European Society of Hypertension and from the European Geriatric Medicine Society

Abstract: The guidelines on hypertension recently published by the European Societies of Hypertension and Cardiology, have acknowledged cognitive function (and its decline) as a hypertension-mediated organ damage. In fact, brain damage can be the only hypertension-mediated organ damage in more than 30% of hypertensive patients, evolving undetected for several years if not appropriately screened; as long as undetected it cannot provide either corrective measures, nor adequate risk stratification of the hypertensive patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 72 publications
0
35
0
2
Order By: Relevance
“… 2 We show that despite the excellent blood pressure control in the SPRINT MIND trial, BPV remains a risk factor for developing cognitive impairment, which is a key outcome for older adults and warrants additional preventative research and routine screening in primary care. 11 …”
Section: Discussionmentioning
confidence: 99%
“… 2 We show that despite the excellent blood pressure control in the SPRINT MIND trial, BPV remains a risk factor for developing cognitive impairment, which is a key outcome for older adults and warrants additional preventative research and routine screening in primary care. 11 …”
Section: Discussionmentioning
confidence: 99%
“…Globally, approximately 17.8 million deaths were attributed to cardiovascular disease, and as a result of aging populations, it is expected to continue increasing [1]. Previous studies have shown that hardening of arterial vessels is associated with an increased risk of cardiovascular complications and dementia [2][3][4][5]. Thus, an early screening of discernable aging of the central or peripheral arteries is an important clinical topic.…”
Section: Introductionmentioning
confidence: 99%
“…Mini-Mental Status Examination (MMSE) 12 The MMSE is a useful, basic screening and evaluation tool (also for follow-ups). It takes 10-15 minutes to administer.…”
Section: Assessment Of Cognitive Functioningmentioning
confidence: 99%